Gene fusions, micro-exons and splice variants define stress signaling by AP2/ERF and WRKY transcription factors in the sesame pan-genome - Parakkunnel, Ramya; Naik K, Bhojaraja; Vanishree, Girimalla; C, Susmita; Purru, Supriya; Bhaskar K, Udaya; Bhat, KV.; Kumar, Sanjay (Frontiers in Plant Science, 2022)
Evolutionary dynamics of AP2/ERF and WRKY genes, the major components of defense response were studied extensively in the sesame pan-genome. Massive variation was observed for gene copy numbers, genome location, domain structure, exon-intron structure and protein parameters. In the pan-genome, 63% of AP2/ERF members were devoid of introns whereas >99% of WRKY genes contained multiple introns. AP2 subfamily was found to be micro-exon rich with the adjoining intronic sequences sharing sequence similarity to many stress-responsive and fatty acid metabolism genes. WRKY family included extensive multi-domain gene fusions where the additional domains significantly enhanced gene and exonic sizes as well as gene copy numbers. The fusion genes were found to have roles in acquired immunity, stress response, cell and membrane integrity as well as ROS signaling. The individual genomes shared extensive synteny and collinearity although ecological adaptation was evident among the Chinese and Indian accessions. Significant positive selection effects were noticed for both micro-exon and multi-domain genes. Splice variants with changes in acceptor, donor and branch sites were common and 6-7 splice variants were detected per gene. The study ascertained the vital roles of lipid metabolism and chlorophyll biosynthesis in the defense response and stress signaling pathways. 60% of the studied genes localized in the nucleus while 20% preferred chloroplast. Unique cis-element distribution was noticed in the upstream promoter region with MYB and STRE in WRKY genes while MYC was present in the AP2/ERF genes. Intron-less genes exhibited great diversity in the promoter sequences wherein the predominance of dosage effect indicated variable gene expression levels. Mimicking the NBS-LRR genes, a chloroplast localized WRKY gene, Swetha_24868, with additional domains of chorismate mutase, cAMP and voltage-dependent potassium channel was found to act as a master regulator of defense signaling, triggering immunity and reducing ROS levels.